Hadits Larangan Tentang Meniup Makanan dan Minuman yang Panas - Alfi Salwa Qibt (IJoIS: Indonesian Journal of Islamic Studies, 2021)
The study aims to discuss the hadith about prohibitions against blowing out hot food and drink. The study is a kind of qualitative through library studies that apply the methods of takhrij and syarah hadith with an approach to health sciences. This study covers a general view of the ban on blowing out food and hot drinks, of hadith about blowing out foods and hot drinks, and hadith analysts about blowing out food and drink in relation to health ethics. The study concluded that a ban on blowing food and hot drinks was associated with health sciences, hadith's status shahih could thus be in Islamic ethics, scholars law the cooking of food and hot drinks as a gusher, and according to health sciences it would enable bacteria from the mouth to enter the food that could lead to disease. The study recommends that hadits experts advance through research along with health professionals on the dangers of blowing hot food and drink and mesosizing their results to the general public.